Convergencia en productividad durante el génesis de la Eurozona (1992-2007): Evidencia empírica de un fenómeno esperado - Garcia-Duch, Miguel (Revista de Economía Mundial, 2017)
This paper examines the three most common notions of convergence – beta, sigma, and times series approaches – applied to the Eurozone since its Maastricht´s design in 1992 until the start of the crisis in 2008. Due to the limitations of the income per capita approach, this paper focuses in general and sectorial productivity per hour convergence. Evidence of convergence is not found at a general level, while the sectorial picture is mixed. Some branches of services suggests convergence but industrial branches points to strong divergence. Within the neoclassical framework, convergence is an expected phenomena, but empirical evidence shows variability in its success. In fact, there is not a general process of productivity convergence among original members of the Eurozone. Hence, some key conclusions are presented in order to develop a more accurate theoretical background.